2009
DOI: 10.2174/157015909788848901
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the Penetration of Blood-Borne Substances into the Brain

Abstract: The blood-brain barrier (BBB) impedes the influx of intravascular compounds from the blood to the brain. Few blood-borne macromolecules are transferred into the brain because vesicular transcytosis in the endothelial cells is considerably limited and the tight junction is located between the endothelial cells. At the first line of the BBB, the endothelial glycocalyx which is a negatively charged, surface coat of proteoglycans, and adsorbed plasma proteins, contributes to the vasculoprotective effects of the ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 90 publications
(99 reference statements)
0
25
0
Order By: Relevance
“…Thus, depending on the extent to which and the site at which circulating 5-HT crosses the blood-brain barrier, it could influence blood pressure by altering the discharge of 5-HT receptor-expressing neurons in cardiovascular regulatory pathways. In contrast with its precursor, 5-HTP, which moves freely across the blood-brain barrier, the current consensus is that 5-HT does not cross the bloodbrain barrier (Hardebo and Owman, 1980;Ohtsuki, 2004;Afergan et al, 2008;Ueno, 2009;Pozdzik et al, 2010). However, a study in 1968 demonstrated that intravenous 5-HT administration results in higher levels of 5-HT and its primary metabolite, 5-HIAA, in the brain (Bulat and Supek, 1968).…”
Section: Central Effects Of 5-hydroxytryptamine Influencing the Sympamentioning
confidence: 99%
“…Thus, depending on the extent to which and the site at which circulating 5-HT crosses the blood-brain barrier, it could influence blood pressure by altering the discharge of 5-HT receptor-expressing neurons in cardiovascular regulatory pathways. In contrast with its precursor, 5-HTP, which moves freely across the blood-brain barrier, the current consensus is that 5-HT does not cross the bloodbrain barrier (Hardebo and Owman, 1980;Ohtsuki, 2004;Afergan et al, 2008;Ueno, 2009;Pozdzik et al, 2010). However, a study in 1968 demonstrated that intravenous 5-HT administration results in higher levels of 5-HT and its primary metabolite, 5-HIAA, in the brain (Bulat and Supek, 1968).…”
Section: Central Effects Of 5-hydroxytryptamine Influencing the Sympamentioning
confidence: 99%
“…The expression of P-glycoprotein (Pgp) on the luminal membrane of brain endothelial microvessel cells has been well characterized (Demeule et al, 2002;Ueno, 2009;Reichel et al, 2011). Various studies have demonstrated that the penetration of a vast variety of drugs across the blood-brain barrier (BBB) is determined by Pgp (Schinkel et al, 1997;Chen et al, 2003;Ose et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the opposite effects of Pgp inhibition on drug transport to the brain and CSF, CSF may not accurately represent the exposures in brain if the compound in CSF is mainly determined by the transport from blood across the BCSFB. Whereas the function of Pgp and Bcrp in regulating drug transport across BBB has been well characterized (Demeule et al, 2002;Daood et al, 2008;Roberts et al, 2008;Ueno, 2009;Reichel et al, 2011), it is still not clear whether Bcrp and Pgp could affect drug transport across the BCSFB. Whether CSF can be used as a surrogate to assess brain exposures of Bcrp and Pgp substrates, therefore, needs to be further examined.…”
Section: Introductionmentioning
confidence: 99%
“…Absorptive mediated endocytosis is based on an electrostatic interaction between negatively charged plasma membrane luminal surfaces (glycocalyx which is a negatively charged proteoglycan or glycosaminoglycan) with cationic substances (e.g. peptides) and uptake it in a vesicle into the endothelial cell and release it on the other side (Figure 4) (Ueno, 2009). This has lower affinity and higher capacity than receptor mediated endocytosis (Alam et al, 2010).…”
Section: Endocytosismentioning
confidence: 99%